Implementasi Pendampingan Legalitas Usaha dan Sertifikasi Halal UMKM Desa Sukamantri untuk Peningkatan Daya Saing Ekonomi Lokal - Faturohman, Ikhsan; Maulana, Diki; Amin, Abdul Mugis Mugni; Nurkhopipah, Nenden; Nursyarifah, Asri; Utami, Aulia Nur; Annisa, Hasna; Khoerunnisa, Rahma; Putri, Carolina Nabila (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The Community Service Program (KKN) of Cipasung University, Tasikmalaya, held in Sukamantri Village aims to increase the awareness and capacity of Micro, Small, and Medium Enterprises (MSMEs) in ensuring business legality and halal certification. This activity includes intensive mentoring covering socialization, data collection, document completion, and registration through the Online Single Submission (OSS) system and a self-declaration halal certification scheme facilitated by the Galunggung Partnership for Sustainable Process Products (LP3H). The results show that 23 micro, small, and medium enterprises (MSMEs) successfully obtained official Business Identification Numbers (NIB). In addition, two businesses have received halal certificates from the Halal Product Guarantee Agency (BPJPH). This achievement demonstrates that students, supporting institutions, the village government, and the community can work together to overcome administrative barriers and digital literacy difficulties faced by MSMEs. This program increases the competitiveness of MSMEs in Sukamantri Village and increases consumer trust in local products.